ANALISIS SOSIAL EKONOMI TERHADAP PENDAPATAN PENGUSAHA TANAMAM HIAS DI KECAMATAN MENGWI KABUPATEN BADUNG - I GUSTI AYU LIA YASMITA; NI RAI ARTINI; NI MADE TAMAN AYUK (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the influence of socioeconomic factors, namely capital, land area, and labor, on the income of ornamental plant entrepreneurs in Mengwi District, Badung Regency. Respondents in this study were determined using a Census method, consisting of 63 ornamental plant entrepreneurs. The data used in this study are primary data. Data collection was conducted through interviews with respondents using structured questionnaires. Hypothesis testing was conducted using various analytical tools, including multiple linear regression analysis, T-test, F-test, preceded by classical assumption tests. The results of the t-test indicate that partially, capital, land area, and labor significantly and positively affect the income of ornamental plant entrepreneurs in Mengwi District, Badung Regency. The results of the F-test indicate that simultaneously, capital, land area, and labor significantly affect the income of ornamental plant entrepreneurs in Mengwi District, Badung Regency. The coefficient of determination (R Square) is 0.847, indicating that the independent variables (capital, land area, and labor) collectively contribute 84.7 percent to the income of ornamental plant entrepreneurs in Mengwi District, Badung Regency. The remaining 15.3 percent is influenced by other factors not explained in this model.